Menkes' Syndrome with Cerebellar Hypoplasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
A 14-month-old boy with Menkes' kinky hair syndrome (MS) associated with deafness and inferior cerebellar vermian hypoplasia was admitted with convulsions and urinary infection at Karadeniz Technical University, Trabzon, Turkey.